The role of artificial intelligence technologies in the learning of students in colleges of education - Ass.lect Sura Hammed Abd Al –Kareem (Journal of College of Education, 2025)
The current research aims to understand the role of artificial intelligence technologies in the learning of education faculty students. To achieve this objective, the researcher formulated the following research question:• What is the role of artificial intelligence technologies in the learning of education faculty students?    To answer this question, the researcher prepared a questionnaire about the role of artificial intelligence in the learning of education faculty students. The questionnaire consisted of 21 items covering all aspects of the research, with responses categorized into three levels: (1) Always, (2) Sometimes, and (3) Never. The validity of the questionnaire was verified by presenting it to a group of specialized professors, and it was then applied to a sample of first-year students, totaling 203 students from the University of Al-Mustansiriyah, College of Education, for the academic year 2024–2025.    The researcher used the descriptive analytical approach and conducted statistical analysis of the data. The findings indicated that students will always use artificial intelligence and that in the era of technology, one cannot do without it. However, the use of artificial intelligence must be approached correctly; otherwise, its use may have negative consequences.
Keywords: Artificial intelligence . learning